Fundamental Causes of Colorectal Cancer Mortality: The Implications of Informational Diffusion - Wang, Andrew (Blackwell Publishing Inc, 2012)
CONTEXT: Colorectal cancer is a major cause of mortality in the United States, with 52,857 deaths estimated in 2012. To explore further the social inequalities in colorectal cancer mortality, we used fundamental cause theory to consider the role of societal diffusion of information and socioeconomic status. METHODS: We used the number of deaths from colorectal cancer in U.S. counties between 1968 and 2008. Through geographical mapping, we examined disparities in colorectal cancer mortality as a function of socioeconomic status and the rate of diffusion of information. In addition to providing year-specific trends in colorectal cancer mortality rates, we analyzed these data using negative binomial regression. FINDINGS: The impact of socioeconomic status (SES) on colorectal cancer mortality is substantial, and its protective impact increases over time. Equally important is the impact of informational diffusion on colorectal cancer mortality over time. However, while the impact of SES remains significant when concurrently considering the role of diffusion of information, the propensity for faster diffusion moderates its effect on colorectal cancer mortality. CONCLUSIONS: The faster diffusion of information reduces both colorectal cancer mortality and inequalities in colorectal cancer mortality, although it was not sufficient to eliminate SES inequalities. These findings have important long-term implications for policymakers looking to reduce social inequalities in colorectal cancer mortality and other, related, preventable diseases.